THE INFLUENCE OF CASH TURNOVER, RECEIVABLES TURNOVER AND INVENTORY TURNOVER ON THE ECONOMIC PROFITABILITY OF REGISTERED PHARMACEUTICAL COMPANIES ON THE INDONESIAN STOCK EXCHANGE PERIOD 2017-2021 - Maya Rahayu; Rico Nur Ilham; Marzuki; Nurainun (PT. Radja Intercontinental Publishing, 2023)
This study examines the effect of cash turnover, receivable turnover, and inventory turnover on the economic rentability of pharmaceutical companies listed on the Indonesia Stock Exchange during 2017-2021. This study uses secondary data, and the samples are 8 pharmaceutical companies listed on the Indonesia Stock Exchange during 2017-2021. The sampling technique used purposive sampling technique. The data analysis method used is the panel data regression analysis method. The results indicate that cash turnover negative and no significantly affects economic rentability, receivable turnover negative and significantly affect economic rentability, and inventory turnover positively and significantly affecnteconomic rentabilityof pharmaceutical companies listed on the Indonesia Stock Exchange for 2017-2021.